The Short Inventory of Problems – Revised (SIP-R): Psychometric properties within a large, diverse sample of substance use disorder treatment seekers - Kiluk, Brian D. (2012)
Assessment of the adverse consequences of substance use serves an important function in both clinical and research settings, yet there is no universally agreed upon measure of consequences relevant to multiple types of substance use disorders. One of the most commonly used measures, the Short Inventory of Problems (SIP), has been adapted and evaluated in several specific populations, but evidence of its reliability and validity across broader samples of persons with substance use disorders is needed. This study evaluated the psychometric properties of a revised version of the SIP (SIP-R) in a large combined sample of alcohol and drug use disorder treatment-seekers, with participants pooled from two national, multisite randomized clinical trials. A total of 886 participants across 10 outpatient treatment facilities completed a common assessment battery that included the SIP-R, Addiction Severity Index (ASI), University of Rhode Island Change Assessment (URICA), HIV Risk Behavior Scale (HRBS), and a substance use calendar. Results supported the SIP-R’s internal reliability (α=.95). Confirmatory factor analysis demonstrated that the hypothesized 5-factor model with one higher-order factor produced the best fit. Convergent validity was evident through the SIP-R’s correlation with several composite scores from the ASI and the URICA, and analyses supported its conceptual distinction from quantity indices of drug/alcohol use. The SIP-R also demonstrated an ability to predict treatment retention, with higher scores associated with poorer retention. These results provide support for the SIP-R’s psychometric properties as a measure of consequences across a broad sample of treatment-seeking drug and alcohol users.